Map of The World Corrected from the Observations Communicated to the Royal Societys of London and Paris, A - Senex, John, d. 1740 (Senex, John d. 1740, 1725)
18th century Copper engraving handcolored with watercolor. Mounted on linen. Full color. Relief shown pictorially. Double hemispheric projection. Printed at top in center: "A Map of The World Corrected from the Observations Communicated to the Royal Societys of London and Paris. By Iohn Senex, F. R. S. Printed beneath title and to the right: "Sold by I. Senex at the Globe against St. Dunstans Church in Fleet Street London 1725." Printed in cartouche beneath title: "To the Right Honourable Richard Boyle, Earl of Burlington and Cork Viscount Dungarvan , Baron Clifford of LAnborough and Baron Boyle of Younghail. This Map is Dedicated by his most Obedient & most humble Servts. Iohn Senex. [Text from previous engraving is visible but not legible.] H. Hulsbergh." Printed around margins and in bottom are texts from The Theory of the Tides from Sir Isaac Newton's "Principia," Edmund Halley's text on the "Quantity of Vapour Exhaled from the Sea, of its Circulation and of the Cause of Springs," and Edmund Halley's text on "An attempt to assigne the Physical cause of the Trade Winds and Monsoons." World map which depicts an outline of Australia as "New Holland," linked to New Guinea. Northwest North America is left blank and California is shown as an island. Notes on lines of magnetic variation as well as notes on exploration are throughout the map. Also noteworthy is the inclusion of the mythical land of Yesso or "Yedso" and the land of Compagnia, northwest of Japan. Arrows for trade winds are shown throughout region between Tropic of Cancer and Tropic of Capricorn. Surrounding the cartouche are four reclining figures, possibly representing the four major continents known at the time, Europe, Asia, Africa and the Americas. Prime Meridian: Isle of Ferro. Scale: 1:40,000,000. John Senex was a surveyor, engraver, publisher and Geographer to Queen Anne. His works include "System of Geography" (with Jeremiah Seller and C. Price), "General Atlas" folio 1708-12, Lawson's "Carolina" (1709), "England Atlas" (1714), Ogilby's "Roads" (1719), "New General Atlas" (1721), Mayo's "Barbados" (1722), Norden's "Hertfordshire" (1723), Budgen's "Sussex" (1724), "First Settlements America" (1735), and "Surrey, Sussex, Kent, Hants., and Berkshire" (1746) (Tooley, 574-6). The land of "Iesso" or "Yezo" was an island allegedly lying north of Japan. Later identified as Hokkaido, explorers in the seventeenth century were unsure of its nature. The Russians attempted to discern whether Yezo was indeed an island or part of Asia with a number of expeditions in the seventeenth century. Under the reign of Peter the Great, the explorers were able to chart Russia's Kamchatka Peninsula and the Kurile Islands. In the 1780s, a French expedition sailed between Yezo and Korea, and then, through the Kuriles (Tooley and Bricker, 130). Source(s): Tooley, Ronald Vere, ed. "The Mapping of America." London: Holland Press, 1985. Tooley, Ronald Vere and Charles Bricker. "Landmarks of Mapmaking: An Illustrated Survey of Maps and Mapmakers." Amsterdam: Elsevier, 1968.